Analysis of Factors Affecting Product Quality in the Process of Electro spun - Abdullayev Azim Rasulovich; Muhammadjonov Muhammadyusuf Shavkatjon o’g’li (Zien Journals, 2022)
The purpose . In this article, the factors and parameters affecting the quality of the product are studied in the process of "Electrospinning" that is used in the production of nanofibers with the help of electricity
Keywords: Electric field; polymer solution; flow rate; viscosity